The role of poly(ADP-ribose) polymerase-1 inhibitor in carrageenan-induced lung inflammation in mice. - Ahmada, Sheikh Fayaz; Zoheir, Khairy M.A.; Ansari, Mushtaq Ahmad; Korashya, Hesham M.; Bakheet, Saleh A.; Ashour, Abdelkader Elbadawy Abbas; Al-Shabanaha, Othman A.; Al-harbi, Mohammed M.; Attiaa, Sabry M. (Elsevier, 2015)
Increasing indication is unveiling a role for poly(ADP-ribose) polymerase (PARP)-1 in the regulation of inflammatory/immune responses. The aim of the present study was to determine the potential anti-inflammatory effects of PARP-1 inhibitor 5-aminoisoquinolinone (5-AIQ) to explore the role of PARP-1 inhibitor in a mouse model of carrageenan-induced lung inflammation. A single dose of 5-AIQ (1.5mg/kg) was administered intraperitoneally (i.p.) 1h before λ-carrageenan (Cg) administration. We assessed the effects of 5-AIQ treatment on CD25(+), GITR(+), CD25(+)GITR(+), IL-17(+) and Foxp3(+) cells which were investigated using flowcytometry in pleural exudates and heparinized blood. We also evaluated mRNA expressions of IL-6, TNF-α, IL-1β, IL-10, CD11a, l-selectin (CD62L), ICAM-1, MCP-1, iNOS and COX-2 in the lung tissue. We further examined the effects of 5-AIQ on the key mediators of inflammation, namely COX-2, STAT-3, NF-kB p65, PARP-1, IkB-α and IL-4 protein expression in the lung tissue using western blotting. The results illustrated that the numbers of T cell subsets, IL-17(+) cytokine levels were markedly increased and Foxp3(+) production decreased in the Cg group. Furthermore, Cg-induced up-regulation of adhesion molecules, pro-inflammatory mediators and chemokine expressions. Western blot analysis revealed an increased protein expressions of COX-2, STAT-3 NF-kB p65 and PARP-1 and decreased IkB-α and IL-4 in the Cg group. PARP-1 inhibitor via 5-AIQ treatment reverses the action significantly of all the previously mentioned effects. Moreover, histological examinations revealed anti-inflammatory effects of 5-AIQ, whereas Cg-group aggravated Cg-induced inflammation. Present findings demonstrate the potent anti-inflammatory action of the PARP-1 inhibitor in acute lung injury induced by carrageenan.